2012
DOI: 10.1111/j.1365-2826.2011.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Cytochrome P450 Aromatase mRNA Expression in the Developing Sheep Brain

Abstract: The intraneuronal conversion of testosterone to estradiol constitutes a critical step in the development and sexual differentiation of the brain of many short gestation mammalian species and has been inferred to play a similar role in long gestation sheep. This conversion is catalyzed by cytochrome P450 aromatase (CYP 19), which is expressed in specific brain structures during fetal development. The present study was undertaken to examine the specific neuroanatomical distribution and relative expression of aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
(96 reference statements)
1
10
0
Order By: Relevance
“…In addition, our anatomical study demonstrated that both ERa and AR are expressed within the central component of the foetal medial preoptic nucleus, which represents the nascent oSDN as defined by aromatase mRNA expression. These results complement our previous observation that aromatase mRNA expression has a similar pattern of distribution in the foetal mPOA, although this is not quantitatively different between the sexes (28). The simultaneous expression of aromatase, ERa and AR suggests that both androgens and oestrogens, either synthesised in the brain or derived from the circulation, are available to mediate the hormone dependent developmental processes that lead to functional and structural changes in brain areas important for male-typical differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our anatomical study demonstrated that both ERa and AR are expressed within the central component of the foetal medial preoptic nucleus, which represents the nascent oSDN as defined by aromatase mRNA expression. These results complement our previous observation that aromatase mRNA expression has a similar pattern of distribution in the foetal mPOA, although this is not quantitatively different between the sexes (28). The simultaneous expression of aromatase, ERa and AR suggests that both androgens and oestrogens, either synthesised in the brain or derived from the circulation, are available to mediate the hormone dependent developmental processes that lead to functional and structural changes in brain areas important for male-typical differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…In the cerebral cortex and amygdala aromatase activity was significantly greater in males than females, but similar sex differences were not observed in the preoptic area or hypothalamus ( Roselli and Resko, 1986 ). Conversely, analysis of fetal sheep brain (at gestational days 53, 65, 85, 100, 120, and 135) by Roselli and Stormshak (2012) revealed that Cyp19 expression levels in the amygdala was similar across days tested in males and females ( Roselli and Stormshak, 2012 ). This study also revealed that both sexes demonstrated a similar temporal pattern of Cyp19 expression in the preoptic area, suggesting that in both non-human primates and sheep aromatase expression in this brain region is not influenced by sexually dimorphic factors.…”
Section: Sex Differences In Aromatase During Critical Periods Of Devementioning
confidence: 97%
“…The expression of P450Arom in the hypothalamus during ontogenesis has been reported in several long gestation species (see Table ) including sheep (Roselli & Stormshak, ), bovine (Peruffo, Cozzi, & Ballarin, ), monkey (Roselli & Resko, ), and man (Sasano et al, ).…”
Section: Discussionmentioning
confidence: 93%